Low Cost Solar Powered Telecenters for Malaysian Rural Areas: Case Study in Pos Sinderut, Pahang, Malaysia - D. Ibrahim, M.; Zainal, S.; K. Othman, A. (International Journal of Engineering and Technology, 2019)
The main objective of this project is to design and analyze the cost benefits solar PV system for rural telecenter. The project focused on designing the main solar system and solar panel energy performance based on translucency. The task that was carried out in this project was the selection of the suitable system that will suit the operation well while keeping the design cost as low as possible. In this project, the design of the solar panel system was focused on the electric loads and its cost benefit. Homer software was used to evaluate the solar panel system. Meant for ways of communications for indigenous people, the Solar Photovoltaic system is one of the popular solution for off-grid rural community power supply. The optimized combination for a particular rural site can be predicted based on NASAâ€™s data of Solar Global Horizontal Irradiance (GHI). In this project, Pos Sinderut was chosen as the site, and the data load was measured. In our preliminary findings, it was found that the model on site was not suitably designed and maintained. The data parameters that was used for the on-site installed model was also not possible to be calculated when the model was simulated using Homer Software. As a result, we proposed a new model design by optimizing the load of VSAT and charging station based on the amount of solar PV and batteries that was supplied. This paper shows the significance of preliminary designs based on the irradiance and the usage load of the specific site before any installation should be commenced. It also showed how the site should be maintained properly in order to ensure a chosen site is sustainable for the rural community, post-installation.Â Â